Circulating soluble urokinase plasminogen activator receptor levels and peripheral arterial disease outcomes. (September 2017) - Samman Tahhan, Ayman; Hayek, Salim S.; Sandesara, Pratik; Hajjari, Jamal; Hammadah, Muhammad; O'Neal, Wesley T.; Kelli, Heval M.; Alkhoder, Ayman; Ghasemzadeh, Nima; Ko, Yi-An; Aida, Hiroshi; Gafeer, Mohamad Mazen; et al.
Abstract: Background and aims: Circulating soluble urokinase plasminogen activator receptor (suPAR) is a marker of immune activation associated with atherosclerosis. Whether suPAR levels are associated with prevalent peripheral arterial disease (PAD) and its adverse outcomes remains unknown and is the aim of the study. Methods: SuPAR levels were measured in 5810 patients (mean age 63 years, 63% male, 77% with obstructive coronary artery disease [CAD]) undergoing cardiac catheterization. The presence of PAD (n = 967, 17%) was classified as carotid (36%), lower/upper extremities (30%), aortic (15%) and multisite disease (19%). Multivariable logistic and Cox regression models were used to determine independent predictors of prevalent PAD and outcomes including all-cause death, cardiovascular death and PAD-related events after adjustment for age, gender, race, body mass index, smoking, diabetes, hypertension, hyperlipidemia, renal function, heart failure history, and obstructive CAD. Results: Plasma suPAR levels were 22.5% ( p  < 0.001) higher in patients with PAD compared to those without PAD. Plasma suPAR was higher in patients with more extensive PAD (≥2 compared to single site) p  < 0.001. After multivariable adjustment, suPAR was associated with prevalent PAD; odds ratio (OR) for highest compared to lowest tertile of 2.0, 95% CI (1.6–2.5) p  < 0.001. In Cox survival analyses adjusted for clinical characteristics and medication regimen, suPAR (in the highest vs. lowest tertile) remained an independent predictor of all-cause death [HR 3.1, 95% CI (1.9–5.3)], cardiovascular death [HR 3.5, 95% CI (1.8–7.0)] and PAD-related events [HR = 1.8, 95% CI (1.3–2.6) p  < 0.001 for all]. Conclusions: Plasma suPAR level is predictive of prevalent PAD and of incident cardiovascular and PAD-related events. Whether SuPAR measurement can help screen, risk stratify, or monitor therapeutic responses in PAD requires further investigation. Highlights: SuPAR is a marker of inflammation, thromobogenesis, and immune regulation. Higher suPAR levels are associated with PAD and are highest in those with extensive atherosclerosis. Higher SuPAR levels are associated with an increase in all-cause and cardiovascular mortality, as well as PAD-related events. Addition of suPAR improved risk discrimination metrics for PAD when added to a model with traditional risk factors.